Integrating network toxicology and transcriptomics to identify CXCL8, EGFR, PTPRC, MYC, and AKT1 as key targets of microplastic-induced miscarriage - Lijia Niu; Xiaoli Zhang; Yiyi Chen; Guifang Song; Jinghui Li; Yixin Xia (Medicine, 2026)
Miscarriage, a prevalent adverse pregnancy outcome linked to maternal-fetal immune dysregulation, is increasingly suspected to be influenced by environmental microplastics, although specific molecular mechanisms remain elusive. This study integrated network toxicology, transcriptomics, and molecular dynamics simulations to elucidate the pathogenic role of microplastics in miscarriage. Initially, network toxicology identified 396 microplastics-related targets, yielding 38 intersection genes with miscarriage-associated targets from GeneCards. Functional enrichment revealed significant involvement in chemokine signaling and cytokine–cytokine receptor interactions. Analysis of the GSE183555 transcriptome dataset pinpointed 5 hub genes: CXCL8, EGFR, PTPRC, MYC, and AKT1. Immune infiltration analysis demonstrated that these hubs correlated significantly with altered immune cell populations, particularly CD8+ Tem cells, while gene set enrichment analysis and gene set variation analysis highlighted their enrichment in interleukin-17, nuclear factor kappa-B, and epithelial-mesenchymal transition pathways. Furthermore, regulatory networks involving specific transcription factors and miRNAs were constructed. Molecular docking confirmed stable binding affinities between hub proteins and potential ligands (e.g., Afatinib for EGFR, Eupalinin A for AKT1), which was further validated by 100-ns molecular dynamics simulations showing consistent root mean square deviation, radius of gyration, and hydrogen bond stability. In conclusion, this multi-omics approach uncovers a critical regulatory axis where microplastics may disrupt pregnancy maintenance by modulating key immune-inflammatory pathways via CXCL8, EGFR, PTPRC, MYC, and AKT1. These findings provide novel mechanistic insights into microplastics-induced reproductive toxicity and identify promising therapeutic targets for preventing environmentally triggered miscarriage, warranting further experimental validation in clinical and animal models.